Effect of cutting positions and growth regulators on rooting ability of Gonystylus bancanus - Ab Shukor, Nor Aini; Guanih, Veronica S.; P., Ismail (Academic Journals, 2010)
The effect of cutting positions and growth regulators on rooting ability ofGonystylus bancanus were studied. This study, aims to determine the effects of cutting positions (top, middle, and bottom) and hormonal treatments (control, Seradix 3, Planton 3000, IBA 100 mg and IBA 150 mg) on the rooting ability of G. bancanus. The top position recorded the highest survival percentage of 90.7% followed by the middle and bottom with values of 86.0 and 74.7%, respectively. Hormonal treatments also showed significant differences (p ≤ 0.05) in which the untreated cuttings survived the highest (93.3%) followed by Planton 3000 (88.9%) and Seradix (83.3%). Top cutting showed the highest rooting percentage of 78.0 followed by middle and bottom positions with percentages of 76.7 and 65.3, respectively. There was no significant difference observed in the rooting ability in terms of hormonal application. However, results in terms of root development based on the number of roots and vigour showed otherwise (significant at p ≤ 0.05), whereby, cuttings from bottom positions treated with IBA 150 mg produced large number of roots which were thicker and healthier.